2022
DOI: 10.1039/d2ta06401d
|View full text |Cite
|
Sign up to set email alerts
|

Aliovalent doping engineering enables multiple modulations of FeS2anodes to achieve fast and durable sodium storage

Abstract: Metal sulfide anodes have trigged extensive academic process for high performance sodium-ion batteries (SIBs). Nevertheless, the poor electronic conductivity and slack diffusion kinetics severely hinder their practical application. Herein, an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…(ii) The doping of S leads to the enlarged interlayer space, which can facilitate ions diffusion and reduce the interface resistance. Besides, the large difference in size between the S atom and the intrinsic atoms in Ni-MOF will cause lattice distortion of Ni-MOF to a certain extent, destroying the periodicity of the lattice and thus resulting in changes in the local electronic structure. , This change can effectively enhance the conductivity of the Ni-MOF electrode. However, high doping concentration will destroy the ordered layered structure, increase the impedance of the electrolyte ions, and eventually result in lower specific capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…(ii) The doping of S leads to the enlarged interlayer space, which can facilitate ions diffusion and reduce the interface resistance. Besides, the large difference in size between the S atom and the intrinsic atoms in Ni-MOF will cause lattice distortion of Ni-MOF to a certain extent, destroying the periodicity of the lattice and thus resulting in changes in the local electronic structure. , This change can effectively enhance the conductivity of the Ni-MOF electrode. However, high doping concentration will destroy the ordered layered structure, increase the impedance of the electrolyte ions, and eventually result in lower specific capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the slopes of the curves fitted with log( i ) and log( v ) at various scan rates, it can be calculated that during the anodic and cathodic processes, the b values are 0.729 and 0.745, respectively (Figure b). Therefore, it can be clearly realized that the electrochemical lithium insertion/extraction behavior of Fe 3 O 4 /FeS@C is presented as both surface-controlled capacitance behavior and diffusion-controlled battery processes. , Moreover, the contribution rates of capacity at different scan rates can be calculated according to eq : , i = k 1 v + k 2 v 1 / 2 where k 1 v and k 2 v 1/2 represent the surface-controlled pseudocapacitive behavior and the diffusion-controlled battery process, respectively. The fitting result of the CV curve at a scan rate of 0.8 mV·s –1 is shown in Figure c, where the area ratio of the shadow region represents the percentage of the capacitance contribution to the total capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, according to the Nyquist plots of the EIS of Fe 3 O 4 @C-12 h, Fe 3 O 4 /FeS@C, and FeS 2 @C materials (Figure 4c), the curves demonstrate that Fe 3 O 4 /FeS@C possesses an obviously lower interfacial resistance compared with Fe 3 O 4 @C-12 h and FeS 2 @C, suggesting its fine reaction kinetics of electronic conductivity and ionic diffusion. 60,61 Furthermore, Figure 4d shows a comparison of the rate performances of the three composites. In the stepped curves, the Fe 3 O 4 /FeS@C composite has more excellent capacities than Fe 3 O 4 @C-12 h and FeS 2 @C, exhibiting the discharge capacities of 913.74, 770.6, 690.1, 637.41, 587.82, and 535.79 mA h•g −1 at various current densities of 200, 400, 800, 1600, 3200, and 6400 mA•g −1 , respectively, and it still offers a capacity of 814.66 mA h•g −1 when the current density drops back to 200 mA•g −1 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, optimizing the adsorption energy of intermediates plays a decisive role in improving the catalytic performance, and the regulation of the electronic structure of the active sites can effectively ameliorate the adsorption free energy of the catalyst for intermediate products [16,17]. Heteroatom doping and the surface vacancy can change the local charge distribution and produce defects, and studies have shown that through their integration, a more optimized electronic state can also be achieved cooperatively [17][18][19]. The construction of a heterojunction can induce charge rearrangement at the interface of the heterojunction and modify the properties of active sites, and recent studies have also identified the key role of heterogeneous catalysts in promoting the lattice oxygen oxidation mechanism (LOM) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%